Star-forming galaxies in the epoch of reionization - Lorenzoni, S (2012)
This work presents a search for galaxies at 6.5 < z < 9.8 based on the Lyman-break technique, using the latest HST WFC3 near-infrared data covering ∼ 150 arcmin^2 of the GOODS-South field. With these data, it is possible to find sufficient z ≈ 7−9 galaxies to fit both φ∗ and M∗ of the UV Schechter luminosity function. There is evidence for evolution in this luminosity function from z = 6−7 to z = 8−9, in the sense that there are fewer UV-bright galaxies at z ≈ 8 − 9, consistent with an evolution mainly in M∗. The candidate z ≈ 7 − 9 galaxies detected have insufficient ionizing flux to reionize the Universe, and it is probable that galaxies below our detection limit provide a significant UV contribution. The faint-end slope, α, is not well constrained. Adopting a similar faint-end slope to that determined at z = 3 − 6 (α = −1.7), and a Salpeter initial mass function, reionization could be achieved at z ≈ 7 for an escape fraction of ionizing photons fesc = 0.5 integrating the luminosity function down to M_UV= −15, while at z ≈ 8, for the same fesc, the ionizing photon budget still falls short even integrating down to M_UV = −8. A steeper faint end slope or a low-metallicity population (or a top-heavy IMF) might still provide sufficient photons for star-forming galaxies to reionize the Universe, but confirmation of this might have to await the James Webb Space Telescope.